POLYACRYLAMIDE GEL ELECTROPHORESIS: A FASTER, EFFICIENT AND AFFORDABLE METHOD FOR DETECTING SSR MARKER POLYMORPHISM IN CASTOR - Agyenim-Boateng K. G.; A. Yeboah J. N. Lu; B. Amankwah Kyei; H. A. Dede; Y. Z. Shi; X. G. Yin (Journal of Animal and Plant Sciences, 2019)
Within a decade, many microsatellite or Simple Sequence Repeats (SSR) markers have been developed  for major crops. These markers have been predicted to lead to greater  innovations in breeding programs and genetic markers development. However, in situations where there is lower variability among markers, genotyping becomes a hurdle. In an experiment to screen for polymorphic primers in castor (Ricinus communis), two methods were employed; 3-5% Agarose gel electrophoresis run at 100-120V for 90 to 120 minutes with Ethidium Bromide staining and 6% Non-denaturing Polyacrylamide gel electrophoresis run at 110V for 90 minutes and silver stained. Gel fingerprints of agarose gel showed unseparated bands, with a lower throughput while gel fingerprints of polyacrylamide gel, showed clear differences between bands even in the lower base pairs with a higher throughput. Polyacrylamide gel electrophoresis proved to give a clearer distinction between bands and separated the bands clearly at a relatively quicker time frame. Health concerns about the carcinogenicity of the bromide stain in agarose gels were also avoided since polyacrylamide gels are silver stained. Polyacrylamide gel electrophoresis can be therefore utilized in further experiments in identifying SSR products with relative ease, lower cost and quicker duration devoid of health concerns.
Keywords: Castor (Ricinuscommunis); Agarose gel; Polyacrylamide gel; SSR markers